Clinical and pathological assessment of 82 patients with cardiovascular diseases undergoing autopsy at the Hospital das Clínicas of the Faculdade de Medicina de Botucatu from 1988 to 1993 - Oliveira, Reinaldo Ayer de [UNESP]; Silva, Marcos Augusto de Moraes [UNESP]; Andrade, Rubens Ramos de [UNESP]; Montenegro, Mário Rubens Guimarães [UNESP] (Sociedade Brasileira de Cardiologia (SBC), 2000)
OBJECTIVE: To evaluated the clinical diagnostic, efficiency for basic death causes in patients dying of circulatory disease and de relative frequency of those diseases. METHODS: Analysis of medical record data of 82 patients, ages from 16 to 84 years old (68 over 40 years old), whose died of circulatory disease and had undergone necropsy in the period from 1988 to 1993 years in the University Hospital of Medicine Faculty of Botucatu-UNESP, Br. RESULTS: The functional class of patients were III or IV, in 78%, and 81.7% needed urgent hospitalization. By the clinical judgment the death were by ischemic heart disease in 32 (21 acute myocardial infarction), Chagas'disease in 12, valvopathy in 11, cardiomyopathy in 7, heart failure with no specification of cardiopathy in 11 and other causes in 9. At the necropsy the death cause was ischemic heart disease in 34 patients, valvopathy in 10, Chagas'disease in 10, cardiomyopathy in 5, and heart failure with no specification of cardiopathy in 2.The concordance taxes were in thhe same order: 94,6%, 90,0%, 83.3%, 71.4% and 28.5%. CONCLUSION: There was a great efficiency of clinical diagnosis for death cause in a general university hospital. The ischemic heart disease were the main causes of death.
Keywords: cardiovascular diseases; autopsy; epidemiology